Practising Japanese Speaking Skills Using Project-Based Learning Model in Online Learning for Senior High School - Chitra Dewi Pertiwi; Didik Nurhadi; Syamsul Sodiq (Universitas Negeri Semarang, 2023)
Implementing learning conducted online during the COVID-19 pandemic forced teachers to be extra creative in using learning models in the learning process, especially in learning Japanese. This research aimed to determine the use of the project-based learning model in training students' speaking skills with an introductory video project as a final assignment and (2) to determine students' responses to learning with a self-introduction video final project to practice speaking skills. The research approach in this study used a qualitative research approach. The research location was the Senior High School of Kawung 1 Surabaya. The subjects in this research were class X students of Senior High School of Kawung 1 Surabaya. The object of this study was a video of introducing oneself and others in Japanese. The data sources in this research were the results of self-introduction video assessment rubrics and questionnaire results. The results of this research indicated that the final project of making a video on learning to speak using the Project Based Learning model was able to train students to speak Japanese fluently, as evidenced by the scores obtained by the students on average, a score of 21. The response given by the participants in giving the final task of making a self-introduction video in practicing speaking skills using the Project Based Learning model was at high criteria, obtained from distributing questionnaires, showing that the average was 24.7 and the highest score was number 29 and the lowest score was at number 21. Keywords : Pendidikan Bahasa Jepang Japanese Education JournalJapanese Online LearningJapanese Speaking Skills